2014
DOI: 10.1149/2.0841414jes
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Model of Bulk Force in a Li-Ion Battery Pack and Its Application to State of Charge Estimation

Abstract: A phenomenological model of the bulk force exerted by a lithium ion cell during various charge, discharge, and temperature operating conditions is developed. The measured and modeled force resembles the carbon expansion behavior associated with the phase changes during intercalation, as there are ranges of state of charge (SOC) with a gradual force increase and ranges of SOC with very small change in force. The model includes the influence of temperature on the observed force capturing the underlying thermal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…14 Separator deformation can be caused during the manufacturing process of the separator or of the battery cell, as well as during operation as a result of internal mechanical stress accumulation during charging [15][16][17][18] and aging. 19,3,20,21 The resulting mechanical deformation of the separator is understood to cause transport restrictions through a pore-closure mechanism, 22,14,23 which can occur in a spatially localized manner due to non-uniform mechanical stresses arising from the cell's architecture 24 as well as spatial variations in local electrode structure and mechanical properties.…”
mentioning
confidence: 99%
“…14 Separator deformation can be caused during the manufacturing process of the separator or of the battery cell, as well as during operation as a result of internal mechanical stress accumulation during charging [15][16][17][18] and aging. 19,3,20,21 The resulting mechanical deformation of the separator is understood to cause transport restrictions through a pore-closure mechanism, 22,14,23 which can occur in a spatially localized manner due to non-uniform mechanical stresses arising from the cell's architecture 24 as well as spatial variations in local electrode structure and mechanical properties.…”
mentioning
confidence: 99%
“…MuKai et al [60] validated that lithium manganese oxide spinels had average coefficients of volumetric thermal expansion by the maximum value of 2.39 × 10 −5 K −1 with X-ray diffraction measurements performed in the temperature range from 100 to 400 K. Because of thermal expansion of cathode, anode, and separator in a cell, Oh and Epureanu [61] found a 5Ah NMC cathode Li-ion cell swelling linearly in the through plane from 25 to 45 • C. Stress generation of a NMC cathode battery stack caused by temperature has been measured by Mohan et al [62], who found the bulky force at the battery stack surface increase with temperature rising from −5 to 45 • C at the same SOC level.…”
Section: Other Factorsmentioning
confidence: 89%
“…Although the availability of published data from in situ electrode stress/strain measurements is limited, factors that influence electrode stress generation also include the effects due to thermal expansion/contraction [60][61][62] and gas generation originated from electrochemical decomposition of electrolyte solvents by the SEI layer formation, high temperature operation, and overcharge [63][64][65]. The winding process of electrodes is the important production technique for Li-ion battery fabrication [66], which can also cause electrode stress generation from external forces and body forces.…”
Section: Other Factorsmentioning
confidence: 99%
“…11 as it most accurately represents our experimental stress relaxations shown in Figure 5a. [11] σ decrease = σ relax = −ct m [12] Combining film growth in Eq. 1-2, 8-9 and stress relaxation in Eq.…”
Section: Effects Of Cycling Ranges On Stress Vs Sohmentioning
confidence: 99%